2007
DOI: 10.1522/030004851
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic behavior of iced cables subjected to mechanical shocks =

Abstract: RESUMEDans les régions froides, les conducteurs de lignes et leurs supports sont directement exposés au givrage atmosphérique. En outre, on s'attend à ce que les températures croissantes dues aux changements climatiques augmentent les risques liés aux événements météorologiques extrêmes qui peuvent augmenter la fréquence et la sévérité des tempêtes de verglas.Plusieurs types de dépôt de glace atmosphérique peuvent charger les câbles aériens : la neige collante, le givre dur, le givre léger et le verglas. Les d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The vibration of a two-span section due to ice shedding from one span was investigated in [5] by considering different types of ice. Reference [6] proposed a model to simulate the mitigation of ice failure and ice shedding in a one-span section due to pulsetype excitation. These models were all elaborated using a commercial finite element analysis software, ADINA [7].…”
Section: Introductionmentioning
confidence: 99%
“…The vibration of a two-span section due to ice shedding from one span was investigated in [5] by considering different types of ice. Reference [6] proposed a model to simulate the mitigation of ice failure and ice shedding in a one-span section due to pulsetype excitation. These models were all elaborated using a commercial finite element analysis software, ADINA [7].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of ncr ’s the C 3i -PU 6endo ’s are related either by D 3 (space group P 3̅ c 1) or C 3i (space group R 3̅) symmetries. Altogether, these four diads of common C 3 axial symmetry, linked by via ncr ’s, form the cornerstone of our study on a network of morphotropism demonstrated by the isostructural groups of n -RPOT derivatives.…”
Section: Discussionmentioning
confidence: 94%
“…The equivalent plastic strain failure criterion proposed by Kalman [32] based on strain and the tensile strength failure criterion proposed by Druez et al [33] based on strength are two kinds of ice-shedding criteria that have been applied in numerical analysis. Phan et al [34] and Laforte et al [35] tested the bending strength and compression strength of the ice coating on the outside of the conductor (ground) wire, it is found that the shear deformation of the ice coating on the outside of the conductor (ground) wire could be ignored.…”
Section: It Can Be Expressed As a Matrixmentioning
confidence: 99%